Residue-resolved insights into the stabilization of therapeutic proteins by excipients: A case study of two monoclonal antibodies with arginine and glutamate - Tobias M. Prass; Patrick Garidel; Lars V. Schäfer; Michaela Blech (mAbs)
Protein formulation development relies on the selection of excipients that inhibit protein–protein interactions preventing aggregation. Empirical strategies involve screening many excipient and buffer combinations by physicochemical characterization using forced degradation or temperature-induced stress, mostly under accelerated conditions. Such methods do not readily provide information on the inter- and intramolecular interactions responsible for the effects of excipients. Here, we describe a combined experimental and computational approach for investigating the effect of protein–excipient interactions on formulation stability, which allows the identification of preferential interaction sites and thus can aid in the selection of excipients to be experimentally screened. Model systems composed of two marketed therapeutic IgG1 monoclonal antibodies with identical Fc domain sequences, trastuzumab and omalizumab, were investigated with commonly used excipients arginine, glutamate, and equimolar arginine/glutamate mixtures. Protein–excipient interactions were studied using all-atom molecular dynamics (MD) simulations, which show accumulation of the excipients at specific antibody regions. Preferential excipient-interaction sites were particularly found for charged and aromatic residues and in the complementary-determining regions, with more pronounced arginine contacts for omalizumab than trastuzumab. These computational findings are in line with the more pronounced stabilizing effects of arginine observed in the long-term storage stability study. Furthermore, the aggregation and solubility propensity predicted by commonly used in silico tools do not align with the preferential excipient-interaction sites identified by the MD simulations, suggesting that different physicochemical mechanisms are at play.